THE COMPARISON OF USING PARAGRAPH FRAME AND SENTENCE COMBINING STRATEGIES TO IMPROVE THE SEVENTH GRADE STUDENTS’ WRITING SKILL AT SMPN 33 PALEMBANG - Ayu Marsela Erda; Yuyun Hendrety (Jurnal Didascein Bahasa, 2018)
The objective of this study was to find out whether or not there was any significant improvement on students’ writing skill between students who used paragraph frame strategy and those who used sentence combining strategy of the seventh grade students at SMPN 33 of Palembang. The research method was quasi-experimental method. The design of this study was non-equivalent control group design. The technique for collecting the data was the test. The population of this study was all Seventh Grade Students of SMPN 33 of Palembang, and the sample of this study was VII.1 and VII.2. The experimental group had 33 students; meanwhile, control group had 35 students. The data were collected by giving pretest, treatment and post-test for both groups. The data were analyzed by using independent and paired sample t-test. The result of the data analysis showed that the mean score of post-test of experimental group was 81.36 and post-test of control group was 63.14. Furthermore, it shows that the value of sig, (2-tailed) was 0.00 and it was lower than 0.05 as the significant level. The value of t-obtained was 4.809 which was higher than t-table critical value of 1.996 and the degree of freedom was 66. Based on the result of data analysis, It can be concluded that there was any significant improvement on students’ writing skill between students who used paragraph frame strategy and those who used sentence combining strategy. Keywords: paragraph frame strategy, sentence combining strategy, writing skill.